Transesterifikasi Minyak Limbah Ikan Patin Menggunakan Isobutanol Dengan Variasi Jumlah Katalis Dan Waktu Reaksi - Risky Deliana; Nirwana Nirwana; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Plastisizer is an organic solvent with high boiling point. As a solid, its melting point is considerably low.  Plastisizer is produced from process called transesterification. It is a reaction between oil (ester) and alcohol, creating new esters and glycerol as it’s by products. This experiment used waste of Pangasius sutchi oil, isobutanol, and H-Zeolit. The transesterification is performed in a reactor equipped with mixer. Independent variables were set prior to the study, consists of molar ratio 1:6,  mixer velocity 175 rpm, and temperature of 90° C. While the dependent variables are reaction rate of 5, 6, and 7 hours, and catalyst amount 10%, 15%, and 20% of oil weight. This experiment resulted in plastisizer with similar characteristics to commercial plastisizer in  specific gravity, viscosity, except saponification value. Furthermore, at reaction rate 6 hours and catalyst amount of 15 %, the conversion of 18,03%. Keywords: H-Zeolit, Isobutanol, Plastisizer, Transesterification